The Actualization of Majelis Taklim Implementation: Challenges and Prospects - Mukhtar Mas’ud (Journal Analytica Islamica, 2023)
This study aims to analyze the actualization of Majelis Taklim implementation in Indonesia by focusing on three main aspects: its institutional foundation, the challenges encountered, and future prospects for its development. This study employs library research with a qualitative-descriptive approach, in which data were collected through the examination of various primary and secondary sources, including laws and regulations, books, scholarly journals, and relevant official documents. The findings indicate that the implementation of Majelis Taklim has a strong legal foundation through Law Number 20 of 2003, Government Regulation Number 55 of 2007, and Minister of Religious Affairs Regulation Number 29 of 2019. Its implementation is also supported by management functions, including planning, organizing, implementation, and supervision, as well as active community participation. Nevertheless, Majelis Taklim faces serious challenges arising from globalization and digital disruption, moral decline within society, and materialistic tendencies that prioritize worldly affairs. This study also formulates future prospects for Majelis Taklim as a center for strengthening faith, reinforcing social and Islamic brotherhood, and serving as a tri-center of religious knowledge within society. The study concludes that strengthening management, improving human resource capacity, and embracing digital transformation are essential for Majelis Taklim to remain relevant and contribute optimally to religious education in Indonesian society.